Panchaetothrips indicus bagnall, a new pest record from Peninsular Malaysia, collected on leaves of Zingiber officinale Rosc. var. Bentong - Ng, Ng; Yong, H.S.; Mound, L.A. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
The Old World genus Panchaetothrips are currently comprises seven species and distributed between Africa, Asia and Australia. Some species were reported as important pest of coffee, arrowroot, banana and turmeric. In this paper, Panchaetothrips indicus, previously known only from India is newly recorded from Peninsular Malaysia, collected on leaves of Zingiber officinale Rosc. var. Bentong. The description is indicating the P. indicus from the specimen taken from Malaysia.